On the link between cold fronts and hail in Switzerland. (27th April 2016) - Schemm, Sebastian; Nisi, Luca; Martinov, Andrey; Leuenberger, Daniel; Martius, Olivia
Abstract: Hail is the costliest atmospheric hazard in Switzerland, causing substantial damage to agriculture, cars and buildings every year. In this study, a 12‐year statistic of objectively identified cold fronts and a radar‐based hail statistic are combined to investigate the co‐occurrence of cold fronts and hail in Switzerland. In a first step, an automated front identification scheme, which has previously been designed for and applied to global reanalysis data, is modified for a high‐resolution regional analysis data set. This front detection method is then adapted, tested and applied to the Consortium for Small Scale Modelling (COSMO) analysis data for the extended hail season (May to September) in the years 2002–2013. The resulting cold front statistic is presented and discussed. In a second step, the frequency of cold fronts is linked to a high‐resolution radar‐based hail statistic to determine the relative fraction of hail initiation events in pre‐frontal environments. Up to 45% of all detected hail events in north‐eastern and southern Switzerland form in pre‐frontal zones. Similar fractions are identified upstream of the Jura and the Black Forest mountains. The percentage of front‐related hail formation is highest in regions where hail is statistically less frequent, with the exception of southern Switzerland. Furthermore, it is shown that fronts create wind‐sheared environments, which are favourable for hail cells.